Authentic Assessment Practice in English Language Teaching based on 2013 Curriculum - Lestari, Ni Putu Diana Eka (English Education Department STKIP Agama Hindu Singaraja, 2023)
The current study aimed at identifying the practice of authentic assessment based on Curriculum 2013. This study was a literature study focusing on identifying the terms of authentic assessment, characteristics of authentic assessment, types of authentic assessment in curriculum 2013, the practice of authentic assessment in EFL context, and the advantages and disadvantages of authentic assessment implementation. This study found that Authentic assessment is model of assessment carried out by the teachers to gather information about the students’ learning performance during the process of learning. This assessment considered to be effective as it helps the students integrate the knowledge and skills, they have learnt with their real life by working on real world tasks, projects, or performances. The strength of conducting authentic assessment allows the students to experience more meaningful learning. However, apart from its strength, this assessment also carries out some weaknesses regarding to its implementation. The weaknesses of this authentic assessment deal with the time-consuming preparation and complexities that lead to the inappropriate implementation. Even so, authentic assessment is still considered to be effective and its practice must be carried out in the classroom, particularly in ELT classroom.